KESEJAHTERAAN PSIKOLOGIS GURU SELAMA PEMBELAJARAN JARAK JAUH DALAM MASA PANDEMIK COVID-19 - Maria Claudia Wahyu Trihastuti (Universitas Katolik Indonesia Atma Jaya, 2021)
Teacher psychological well-being is the level of teacher satisfaction regarding the experience of carrying out a role as a teacher including a sense of optimism, a sense of being able to control life and self-determination, environmental mastery and self-efficacy, growth and meaningful activities during distance learning in the covid-19 pandemic. The purpose of this study was to obtain information about the level of psychological well-being of teachers and to obtain information about the most dominant and less dominant components of psychological well-being experienced by teachers during distance learning. This type of research is descriptive research with a survey research design through a rating scale instrument. The subjects were 91 teachers. The results showed that most of the teachers had a high and very high level of psychological well-being. The most dominant components are components of environmental mastery and self-efficacy as well as components of growth and meaningful activities. While the less dominant component is the sense of being able to control life and self-determination and the component of optimism.